Influence of irregular heart rhythm on radiation exposure, image quality and diagnostic impact of cardiac computed tomography angiography in 4,339 patients: data from the German Cardiac Computed Tomography Registry - Korosoglou, Grigorios; Katus, Hugo (Journal of cardiovascular computed tomography, 2018)
Background Coronary computed tomography angiography (coronary CTA) provides non-invasive evaluation of the coronary arteries with high precision for the detection of significant coronary artery disease (CAD). Aim To investigate whether irregular heart rhythm including atrial fibrillation and premature beats during data acquisition influences (i) radiation and contrast media exposure, (ii) number of non-evaluable coronary segments and (iii) diagnostic impact of coronary CTA. Methods Twelve tertiary care centers with ≥64 slice CT scanners and ≥5 years of experience with cardiovascular imaging participated in this registry. Between 2009 and 2014, 4339 examinations were analysed in patients who underwent clinically indicated coronary CTA for suspected CAD. Clinical and epidemiologic data were gathered from all patients. In addition, clinical presentation, heart rate and rhythm during the scan, Agatston score, radiation and contrast media exposure and the diagnostic impact of coronary CTA were systematically analysed. Results Of 4339 patients in total, 260 (6.0%) had irregular heart rhythm, whereas the remaining 4079 (94.0%) had stable sinus rhythm. Patients with irregular heart rhythm were older (63.2 ± 12.5yrs versus 58.6 ± 11.4yrs. p < 0.001), exhibited a higher rate of pathologic stress tests before CTA (37.1% versus 26.1%, p < 0.01) and higher heart rates during CTA compared to those with sinus rhythm (62.5 ± 11.6bpm versus 58.9 ± 8.5bpm, p < 0.001). Both contrast media exposure and radiation exposure were significantly higher in patients with irregular heart rhythm (90 mL (95%CI = 80-110 mL) versus 80 mL (95%CI = 70-90 mL) and 6.2 mSv (95%CI = 2.5-11.7) versus 3.3 mSv (95%CI = 1.7-6.9), p < 0.001 for both). Coronary CTA excluded significant CAD less frequently in patients with irregular heart rhythm (32.9% versus 44.8%, p < 0.001). This was attributed to the higher rate of examinations with at least one non-diagnostic coronary segment in patients with irregular heart rhythm (10.8% versus 4.6%, p < 0.001). Subsequent invasive angiography could be avoided in 47.2% of patients with irregular heart rhythm compared to 52.9% of patients with sinus rhythm (p = NS), whereas downstream stress testing was recommended in 3.2% of patients with irregular heart rhythm versus 4.0% of patients with sinus rhythm (p = NS). Conclusion A significant number of patients scheduled for coronary CTA have irregular heart rhythm in a real-world clinical setting. In such patients, heart rate during coronary CTA is higher, possibly resulting in (i) higher radiation and contrast agent exposure and (ii) more frequent coronary CTA examinations with at least one non-diagnostic coronary artery segment. However, this does not seem to lead to increased downstream stress testing or subsequent invasive procedures.